Development of a chemical-free technology for control of membrane biofouling - Kua, Shi Ting. (2013)
In this study, feasibility and the effectiveness of microbubbles as a form of chemical-free technology for control of membrane biofouling was investigated. Experiments were designed to evaluate the removal efficiency of biofilms developed on membrane surfaces with microbubbles. Results showed that microbubbles raised the treatment efficiency significantly for control of membrane biofouling as compared to conventional chemical methods.